A TRMM/GPM retrieval of the total mean generator current for the global electric circuit. Issue 18 (25th September 2017) - Peterson, Michael; Deierling, Wiebke; Liu, Chuntao; Mach, Douglas; Kalb, Christina
Abstract: A specialized satellite version of the passive microwave electric field retrieval algorithm (Peterson et al., 2015) is applied to observations from the Tropical Rainfall Measuring Mission (TRMM) and Global Precipitation Measurement (GPM) satellites to estimate the generator current for the Global Electric Circuit (GEC) and compute its temporal variability. By integrating retrieved Wilson currents from electrified clouds across the globe, we estimate a total mean current of between 1.4 kA (assuming the 7% fraction of electrified clouds producing downward currents measured by the ER‐2 is representative) to 1.6 kA (assuming all electrified clouds contribute to the GEC). These current estimates come from all types of convective weather without preference, including Electrified Shower Clouds (ESCs). The diurnal distribution of the retrieved generator current is in excellent agreement with the Carnegie curve (RMS difference: 1.7%). The temporal variability of the total mean generator current ranges from 110% on semi‐annual timescales (29% on an annual timescale) to 7.5% on decadal timescales with notable responses to the Madden‐Julian Oscillation and El Nino Southern Oscillation. The geographical distribution of current includes significant contributions from oceanic regions in addition to the land‐based tropical chimneys. The relative importance of the Americas and Asia chimneys compared to Africa is consistent with the best modern ground‐based observations and further highlights the importance of ESCs for the GEC. Key Points: The estimated GEC generator current is 1.4‐1.6 kA The generator current varies primarily with the (semi) annual cycle and diurnal cycle, but ENSO and MJO signals are noted The estimated generator current varies least on decadal (7.5%) and weekly (2%) time scales and the latter is likely not a global signal Plain Language Summary: Electrified weather across the globe powers the Global Electric Circuit (GEC) that regulates the electrical potential of the ionosphere. As it is impossible to measure the current provided by every electrified cloud directly, we use a retrieval algorithm to quantify this current from Tropical Rainfall Measuring Mission (TRMM) and Global Precipitation Measurement (GPM) satellite measurements. We then examine the variability of this generator current on time scales that range from one day to more than a decade.We estimate that electrified weather provides an average current of 1.4 kA and 1.6 kA globally. Though current contributions can be found in land and ocean regions across the globe, large concentrations are found in the tropics near the equator and in the "tropical chimneys" of the Americas, Africa, and Asia. The greatest source of variability in the GEC generator current is on the semi‐annual time scale (110%) followed by local hour (58%), and universal time (34% ‐ Carnegie curve). The smallest variations are on the decadal (7.5%) and weekly (2%) time scales.